Pre-treatment or Post-treatment of Human Glioma Cells With BIX01294, the Inhibitor of Histone Methyltransferase G9a, Sensitizes Cells to Temozolomide - Ciechomska, Iwona Anna; Marciniak, Marta Patrycja; Jackl, Judyta; Kaminska, Bozena (Frontiers in Pharmacology, 2018)
Glioblastoma (GBM) is a malignant, primary brain tumor, highly resistant to conventional therapies. Temozolomide (TMZ) is a first line therapeutic agent in GBM patients, however, survival of such patients is poor. High level of DNA repair protein, O6-methylguanine-DNA-methyltransferase (MGMT) and occurrence of glioma stem-like cells contribute to GBM resistance to the drug. Here, we explored a possibility of epigenetic reprograming of glioma cells to increase sensitivity to TMZ and restore apoptosis competence. We combined TMZ treatment with BIX01294, an inhibitor of histone methyltransferase G9a, known to be involved in cancerogenesis. Two treatment combinations were tested: BIX01294 was administered to human LN18 and U251 glioma cell cultures 48 h before TMZ or 48 h after TMZ treatment. Despite their different status of the MGMT gene promoter, there was no correlation with the response to TMZ. The analyses of cell viability, appearance of apoptotic alterations in morphology of cells and nuclei, and markers of apoptosis, such as levels of cleaved caspase 3, caspase 7 and PARP, revealed that both pre-treatment and post-treatment with BIX01294 sensitize glioma cells to TMZ. The additive effect was stronger in LN18 cells. Moreover, BIX01294 enhanced the cytotoxic effect of TMZ on glioma stem-like cells, although it was not associated with modulation of the pluripotency markers (NANOG, SOX2, CD133) expression or methylation of NANOG and SOX2 gene promoters. Accordingly, knockdown of methyltransferase G9a augments TMZ-induced cell death in LN18 cells. We found the significant increases of the LC3-II levels in LN18 cells treated with BIX01294 alone and with drug combination that suggests involvement of autophagy in enhancement of anti-tumor effect of TMZ. Treatment with BIX01294 did not affect methylation of the MGMT gene promoter. Altogether, our results suggest that G9a is a potential therapeutic target in malignant glioma and the treatment with the G9a inhibitor reprograms glioma cells and glioma stem-like cells to increase sensitivity to TMZ and restore apoptosis competence.